Analisis Pengaruh Kualitas Pelayanan, dan Promosi Terhadap Penjualan Pada Toko Thrift Shop Sandang 69 Bandar Lampung - Muhamad Robel Akbar Ya’cub; M. Emil Rachman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to determine the effect of service quality and promotion on sales at Thrift Shop Clothing 69 Bandar Lampung. This research is associative in nature which aims to determine the relationship between two or more variables that function to explain, predict, and control phenomena. Respondents in this study were customers of thrift shop Sadang 69, totaling 50 respondents. The data analysis technique in this study used multiple linear regression analysis. The data testing process is assisted by the SPSS 25.0 application program. According to the partial test results, service quality has a positive and significant effect on sales, promotion has a positive and significant effect on sales, and simultaneous testing shows that service quality and promotion have a positive and significant effect on sales at the Thrift Shop Clothing Store 69 Bandar Lampung.